Knowledge, Practice and Attitude of Women Regarding Breastfeeding in Thi-Qar Governorate-Iraq - Fatima K. Naeam; Amer Abdullah Sachit; Hayfaa M. Mones (Acta Medica Iranica)
Breastfeeding (BF) is the natural way for infants’ nutrition, it provides the ideal nutrients they need for healthy development and growth. The purpose of this study was to evaluate mothers' knowledge and practice of BF and its determinants and to determine the association between knowledge and certain characteristics. 200 moms who were patients at the Bint Al-Huda teaching hospital between November 1, 2021, and February 1, 2021, were chosen at random with their consent for this cross-sectional study, and their answers to a standardized questionnaire were analyzed. Of the 200 women, 26% were between the ages of 20 and 25, with a mean and SD of 29.24±7.829 and 24.5% having completed elementary school. Prior to our study, nearly (67%) mothers had received education on BF. A mother who practices breast cancer has a low risk of developing the disease (62.5%). Proper positioning is also important for achieving effective breast cancer (68.5%). Breastfeeding should begin within 30 minutes of delivery (62%), and once the baby begins taking complementary foods (54.5%), mothers can combine breastfeed and formula feeding. We found that most mothers had engaged in exclusive BF and knew only a moderate amount about its benefits. Better educational initiatives are required to raise public awareness of its long-term benefits for the nation's health status.